IMPROVEMENT OF HUMAN RESOURCES COMPETENCE WITH ACADEMIC QUALITY POLICY IN THE ECONOMIC SECTOR OF HIGHER EDUCATION PROVIDERS IN EAST JAVA - Sutrisno (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2021)
This research aims to analyze and obtain a description of the improvement of HR competencies with the Academic Quality Policy in the Economic Sector of Higher Education Providers in East Java. The method used in this research is descriptive method with a qualitative approach. The results showed that the implementation of academic services carried out by all components of higher education including lecturers, staff and academic staff showed a change towards better improvement, in terms of human resource management, as well as supporting facilities that support the implementation of improving the quality of academy services. Higher education institutions need to control the quality of activities carried out at stages in the management process which include input, process, output and stakeholder satisfaction. Improving the quality of service can be carried out by applying in the service quality management process, perfecting and strengthening the curriculum, updating and perfecting learning facilities, increasing the quality qualifications and the number of human resources that are adjusted to the needs in higher education.